2001
DOI: 10.1086/321499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dust Extinction on Estimating the Star Formation Rate of Galaxies: Lyman Continuum Extinction

Abstract: We reexamine the effect of Lyman continuum (λ ≤ 912Å) extinction (LCE) by dust in H ii regions in detail and discuss how it affects the estimation of the global star formation rate (SFR) of galaxies. To clarify the first issue, we establish two independent methods for estimating a parameter of LCE (f), which is defined as the fraction of Lyman continuum photons contributing to hydrogen ionization in an H ii region. One of those methods determines f from the set of Lyman continuum flux, electron density and met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 47 publications
8
86
1
Order By: Relevance
“…Other ratios of stellar to nebular attenuation can certainly be considered, but this serves to exemplify the EW(Hβ) and β trends. The resulting LyC depletion factor is somewhat lower than suggested by Inoue (2001) and Inoue et al (2001) for local H ii regions, but similar to that derived by Hirashita et al (2003) for low-redshift starburst galaxies. Our procedure gives rise to the dashed attenuation arrows in Figure 9.…”
Section: Dust Effects In the Ew(hβ)-β Diagramsupporting
confidence: 85%
See 1 more Smart Citation
“…Other ratios of stellar to nebular attenuation can certainly be considered, but this serves to exemplify the EW(Hβ) and β trends. The resulting LyC depletion factor is somewhat lower than suggested by Inoue (2001) and Inoue et al (2001) for local H ii regions, but similar to that derived by Hirashita et al (2003) for low-redshift starburst galaxies. Our procedure gives rise to the dashed attenuation arrows in Figure 9.…”
Section: Dust Effects In the Ew(hβ)-β Diagramsupporting
confidence: 85%
“…However, if the dust is spatially mixed with the H ii gas as in Figures 8(c) and (d), some fraction of the LyC photons will be absorbed by dust before they have a chance to ionize the gas (e.g., Inoue et al 2001;Inoue 2001) and this will not be revealed by the Balmer line ratios. While radiation pressure and dust sublimation act to produce a dust cavity around the ionizing stars, neither of these effects is sufficiently strong to prevent LyC photons from getting absorbed directly by dust in local H ii regions (Inoue 2002).…”
Section: Dust Distributionsmentioning
confidence: 99%
“…There are two components to consider for the absorption of UV-to-NIR photons: the stellar continuum from l m < < 0.0912 2.85 m, which will be characterized by the attenuation curve, and ionizing photons (l m < 0.0912 m) absorbed by dust either directly or after they have been re-emitted by hydrogen through recombination lines. In practice, this comparison is quite difficult owing to the large uncertainty in calculating the fraction of ionizing photons directly absorbed by dust (e.g., Inoue et al 2001;Hirashita et al 2003).…”
Section: Energy Balance Comparisonmentioning
confidence: 99%
“…This estimate is with the assumption of optically thin emission and hence serves as a lower limit as the emission could be optically thick at 1280 MHz. Various studies in the literature have shown that dust absorption of Lyman continuum photons can be very high (Inoue et al 2001;Arthur et al 2004;Paron et al 2011). With limited knowledge of the dust properties, we have not accounted for the dust absorption here.…”
Section: Ionized Emissionmentioning
confidence: 99%